2014
DOI: 10.1504/ijebr.2014.064118
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stock market development and inflation on economic growth in India: evidence using the ARDL bounds testing and VECM approaches

Abstract: This paper investigates the impact of stock market development, money supply and inflation on economic growth in India during the post-globalisation era of the 1990s, especially during the period from 1994 to 2012. Using autoregressive distributive lag (ARDL) bounds testing approach, the study finds stock market development, money supply, inflation and economic growth are cointegrated, suggesting the presence of a long-run equilibrium relationship between them. The vector autoregressive error correction model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The stock index is also influential on the inflation rate. Pradhan et al (2014) and Prieto and Lee (2019) found a long-term relationship between the stock index and inflation. Apparently, when the stock market index rises, economic activity increases productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The stock index is also influential on the inflation rate. Pradhan et al (2014) and Prieto and Lee (2019) found a long-term relationship between the stock index and inflation. Apparently, when the stock market index rises, economic activity increases productivity.…”
Section: Introductionmentioning
confidence: 99%